Bad Kitty Goes to the Vet - Bruel, Nick (New York : Roaring Brook Press, 2016)
"Even the best bad kitties can get sick, and when it happens, it means just one thing: a visit to the vet"--
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Bad Kitty -- (Fictitious character from Nick Bruel) -- Fiction; Cats -- Juvenile fiction; Veterinarians -- Juvenile fiction; Cats -- Fiction; Veterinarians -- Fiction; Humorous stories; JUVENILE FICTION / Animals / Cats; JUVENILE NONFICTION / Humor / General